Does Good Financial Development Attract Tourists? Evidence From ASEAN Countries - Panjaitan, Makmur Tradesman Hasudungan (Journal of Developing Economies, 2022)
This study aims to examine the effect of financial development on tourism demand in member countries of Association of Southeast Asian Nations (ASEAN). The indicators are financial development index; financial institution depth index; financial institutional access index; and financial institutions efficiency index. Several control variables employed in this study are consumer price index, health expenditure, poor air quality, and trade openness. This study uses panel data between 2010 and 2018 from 10 ASEAN countries. Data are sourced from international institutions such as the World Bank, United Nation of World Tourism Organization (UNWTO), International Monetary Fund (IMF), and World Health Organization (WHO). The method used in the analysis is the static panel data regression. The results show that financial development has a positive effect on tourism demand. In terms of control variables' impact, consumer price index, health expenditure and trade openness have a positive impact, whereas poor air quality has a negative impact. The current study's implication on policy making is to develop the financial sector by increasing the number of ATMs and improving the mobile banking facilities